1984
DOI: 10.1042/bj2170073
|View full text |Cite
|
Sign up to set email alerts
|

The preparation and characterization of vitellogenin messenger RNA from rainbow trout (Salmo gairdneri)

Abstract: Agarose-gel electrophoresis of polyadenylated RNA from livers of oestrogen-treated male rainbow trout revealed a major high-Mr species (7200 nucleotides), which is absent from the polyadenylated RNA isolated from hormonally unstimulated male trout liver. Translation in vitro of the RNA from oestrogen-treated males in a mRNA-dependent rabbit reticulocyte lysate produced a protein (Mr 200 000) that could be immunoprecipitated with antibodies against trout serum vitellogenin, but no immunoprecipitable protein was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

1987
1987
2011
2011

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(7 citation statements)
references
References 31 publications
1
6
0
Order By: Relevance
“…This result corroborates the recent report of Kishida et al (1992), who used DEAE-agarose to purify an s-VTG with an apparent 170 kDa primary subunit from blood plasma of E 2 -induced striped bass. This value is very similar to estimates of the molecular weight (170-200 kDa) of the rainbow trout VTG monomer (Chen 1983;Valotaire et al 1984), and similar to VTG subunit molecular weights (85-200 kDa) reported for several other fishes (tabulated by Mommsen and Walsh 1988;Silversand and Haux 1989;Bradley and Grizzle 1989;Ding et al 1989).…”
Section: Sampling Monthsupporting
confidence: 73%
“…This result corroborates the recent report of Kishida et al (1992), who used DEAE-agarose to purify an s-VTG with an apparent 170 kDa primary subunit from blood plasma of E 2 -induced striped bass. This value is very similar to estimates of the molecular weight (170-200 kDa) of the rainbow trout VTG monomer (Chen 1983;Valotaire et al 1984), and similar to VTG subunit molecular weights (85-200 kDa) reported for several other fishes (tabulated by Mommsen and Walsh 1988;Silversand and Haux 1989;Bradley and Grizzle 1989;Ding et al 1989).…”
Section: Sampling Monthsupporting
confidence: 73%
“…These pot halves acted as spawning substrata, without which the fish would not spawn. Fish were exposed to treatments for a total of 42 d. Spawning substrata were removed for 7 d (days [22][23][24][25][26][27][28][29] to allow the fish to rest and then returned for the final 2 weeks of the exposure. The aquaria were randomly assigned to receive treatment concentrations of NP or control solutions delivered by a proportional-flow diluter.…”
Section: Exposuresmentioning
confidence: 99%
“…In cyprinid fishes such as the roach (Rutilus rutilus L.), which spawns once in a reproductive season, and in bleak (Alburnus albrunus L.) and white bream (Blicca bjoerkna L.), which have multiple spawnings per season, plasma Vtg concentrations were weakly yet positively correlated with plasma E 2 concentrations [26]. Induction of Vtg has been suggested to be a sensitive, E 2 -specific biomarker [8,[27][28][29] for the exposure of oviparous animals, such as the fathead minnow, to estrogen agonists [30], and it has been used to monitor for exposure of fish to endogenous estrogens, exogenous estrogens, and xenoestrogens [3,12,31]. However, in those experiments, a relatively great increase in plasma E 2 concentration resulted in a rather modest increase in plasma Vtg concentration.…”
Section: Relationship Between Plasma E 2 and Vtgmentioning
confidence: 99%
“…44 By denaturing conditions of SDS-PAGE, the monomeric form of Salmo gairdneri Vtg was found to range from 170 kDa 45 to 200 kDa. 46 Ding et al 47 reported two forms of Vtg of monomeric sizes, 130 and 180 kDa in the evolutionarily more advanced teleost fish, O. aureus. Vtg variation studied in 11 species of Perciformes, encompassing the families Cichlidae, Serranidae, Lutjanidae, Centropomidae, and Eleotrididae confirmed that in this order of fish the main features of Vtg protein diversity are interfamily variability in size and subunit number.…”
Section: Vitellogenin Proteins -Interspecific Diversity In Molecular mentioning
confidence: 98%